2008
DOI: 10.1161/circresaha.108.179408
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidant Stress on AT1 Receptor Expression in Neurons of Rabbits With Heart Failure and in Cultured Neurons

Abstract: Abstract-We have previously reported that the expression of Angiotensin II (Ang II) type 1 receptors (AT1R) was increased in the rostral ventrolateral medulla (RVLM) of rabbits with chronic heart failure (CHF) and in the RVLM of normal rabbits infused with intracerebroventricular (ICV) Ang II. The present study investigated whether oxidant stress plays a role in Ang II-induced AT1R upregulation and its relationship to the transcription factor activator protein 1 (AP1) in CHF rabbits and in the CATHa neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 53 publications
5
54
1
1
Order By: Relevance
“…We did not measure AT 1 R and AT 2 R expression in the current study. Our previous work clearly showed that ANG II upregulates AT 1 R transcription and protein expression at 100 nM within 4 h in this neuronal cell line (21,22). Recent work by Herrera et al (11) has called into question the validity of AT 1 R measurements, at least in mice, because of nonspecificity of commercial antibodies.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We did not measure AT 1 R and AT 2 R expression in the current study. Our previous work clearly showed that ANG II upregulates AT 1 R transcription and protein expression at 100 nM within 4 h in this neuronal cell line (21,22). Recent work by Herrera et al (11) has called into question the validity of AT 1 R measurements, at least in mice, because of nonspecificity of commercial antibodies.…”
Section: Discussionmentioning
confidence: 76%
“…The Src family of protein tyrosine kinases has been shown to play a key role in the coupling of cell surface receptors with MAPK activation (14,27) and NADPH oxidase-derived O 2 ·Ϫ , which also serves as a second messenger downstream of the AT 1 R for MAPK activation (5,14). Our laboratory has shown that ANG II induces O 2 ·Ϫ production through AT 1 R and NADPH oxidase activation in CATH.a neurons (21). Therefore, O 2 ·Ϫ may also participate in the regulation of ACE and ACE2 expression.…”
Section: Discussionmentioning
confidence: 84%
“…1,30 The novel aspect of this study is that it elucidates the mechanism for Ang II-mediated NHE3 stimulation. We demonstrate that, in BSO-treated rats, which exhibit oxidative stress and high blood pressure, the Ang II-induced NHE3 stimulation is significantly higher than normotensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…31 Nevertheless, these data confirm previous findings that oxidative stress could be an independent risk factor to the development of hypertension by exaggerating AT 1 R expression, response, and stimulation of renal sodium transporters. 1,30,[32][33][34] Ang II via AT 1 Rs activates serine/threonine and tyrosine kinase pathways, both of which can regulate NHE3 activity. 1,15,20,28 The serine/threonine kinases are activated via PLC stimulation, and our data show that D609 and ET-18-OCH3 (PLC inhibitors) abolished Ang II-induced NHE3 stimulation, indicating the involvement of PLC pathways.…”
Section: Discussionmentioning
confidence: 99%
“…How PPARb activation reduces AT 1 expression remains unknown. Several reports have demonstrated that AngII in the rostral ventrolateral medulla induced long-term pressor actions via upregulation of the AT 1 receptor gene in a series of molecular events involving O 2 2 production from NADPH oxidase after AT 1 receptor activation (Chan et al, 2007;Liu et al, 2008). We found that chronic activation of PPARb increased RGS5 expression, which also interfered with the AngII-AT 1 signaling pathway in the brain, reducing NADPH oxidase activity and the subsequent AT 1 receptor overexpression, suggesting an important role of brainstem RGS5 in the antihypertensive effects of oral GW0742 in AngII-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%